2021
DOI: 10.3389/fmicb.2021.715545
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Quinvirus in the Family Betaflexiviridae That Infects Winter Wheat

Abstract: Yellow mosaic disease in winter wheat is usually attributed to the infection by bymoviruses or furoviruses; however, there is still limited information on whether other viral agents are also associated with this disease. To investigate the wheat viromes associated with yellow mosaic disease, we carried out de novo RNA sequencing (RNA-seq) analyses of symptomatic and asymptomatic wheat-leaf samples obtained from a field in Hokkaido, Japan, in 2018 and 2019. The analyses revealed the infection by a novel betafle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 82 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…When a small RNA dataset derived from wheat cv. “Kitahonami” infected with a betaflexivirus [ 35 ] or “Chinese Spring” [ 36 ] uninfected with WhCV1 was analyzed, no small RNA read was mapped to the 3′-terminal end of the WhCV1-WL19a negative-strand genomic RNA (data not shown), suggesting that the abundant 22-nt small RNAs were specifically derived from WhCV1 RNAs and probably not from the host plant.…”
Section: Resultsmentioning
confidence: 99%
“…When a small RNA dataset derived from wheat cv. “Kitahonami” infected with a betaflexivirus [ 35 ] or “Chinese Spring” [ 36 ] uninfected with WhCV1 was analyzed, no small RNA read was mapped to the 3′-terminal end of the WhCV1-WL19a negative-strand genomic RNA (data not shown), suggesting that the abundant 22-nt small RNAs were specifically derived from WhCV1 RNAs and probably not from the host plant.…”
Section: Resultsmentioning
confidence: 99%
“…Wheat viruses continue to pose a major threat to wheat production and global food security [ 32 ]. Recently, various HTS platforms have been utilized for detecting undocumented or newly putative viruses and for complete virome analysis in wheat [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. However, no studies have been reported identifying wheat-infecting viruses in Korea; therefore, we aimed to determine the composition of the wheat virome by utilizing field samples from three major domestic wheat-producing regions through two HTS platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, HTS has been widely applied to plant virology, leading to a signi cant increase in the discoveries of novel plant viruses [13] as well as in wheat new emerging plant viruses are constantly being identi ed [14][15][16]. In our study, the genome organization of TaAVLV1 detected from wheat leaves hasn't evolved to obtain any sequences for encoding any coat protein (CP) or movement protein (MP), but shared a lot of similarity to fungal viruses.…”
Section: Sequence Propertiesmentioning
confidence: 99%